2015
DOI: 10.1093/abbs/gmv010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and expression of Pen-2 in the central nervous system of APP/PS1 double transgenic mice

Abstract: The γ-secretase complex catalyzes the final cleavage step of amyloid β-protein precursor (APP) to generate amyloid β (Aβ) peptide, a pathogenic component of senile plaques in the brain of Alzheimer's disease (AD) patients. Recent studies have shown that presenilin enhancer-2 (Pen-2), presenilin (PS, including PS1 and PS2), nicastrin, and anterior pharynx-defective 1 are essential components of the γ-secretase. The structure and function of Pen-2 in vitro have been well defined. However, little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…Nevertheless, our small IHC experiment showed that in a brain with ADNC, PEN-2 was highly expressed in the hippocampus and substantia nigra. In contrast to findings in mouse models of AD, we did not see expression in cerebellum and pons [ 68 ].…”
Section: Resultscontrasting
confidence: 99%
“…Nevertheless, our small IHC experiment showed that in a brain with ADNC, PEN-2 was highly expressed in the hippocampus and substantia nigra. In contrast to findings in mouse models of AD, we did not see expression in cerebellum and pons [ 68 ].…”
Section: Resultscontrasting
confidence: 99%
“…PEN-2 is widely expressed in specific nerve cells of most brain areas of transgenic APP/PS1 mice, including the olfactory bulb, basal ganglia, striatum, cortex, hippocampus, amygdala, thalamus, hypothalamus, cerebellum, brainstem, and spinal cord. It is not only the main component of γ -secretase, but also the modulator of γ -secretase activity, playing a key role in the production of A β 1-42 [ 21 23 ]. CREB, a transcription regulatory factor of PEN-2, which can activate some specific genes to produce proteins, strengthens the connection between cells and is closely related to the formation and maintaining of long-term memory [ 24 ].…”
Section: Discussionmentioning
confidence: 99%